Training needs for self-management skills in the light of some variables "A field study on a sample of female classroom teachers in the first cycle schools in the city of Jableh" - رضوان, رهف; ريم كحيلة, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research aimed to identify the degree of training needs for self-management skills on a sample of classroom teachers in the city of Jableh, and to study the differences between them in the degree of training needs for these skills according to the following variables: (years of experience, educational qualification, whether or not to undergo training courses in the fields of human development). The research sample consisted of (168) female classroom teachers in the city of Jableh. The researcher used the descriptive approach, and a questionnaire was built to measure the training needs for self-management skills. The results showed that the sample members have high training needs for the self-management skills. The results also indicated that there were statistically significant differences between the sample members in their training needs for the self-management skills according to the variable of years of experience in favor of teachers with less than five years of experience, and according to the educational qualification variable in favor of teachers who obtained a bachelor's degree in education, and according to the variable whether or not to undergo training courses in the fields of human development in favor of teachers who are not subject to such courses.